Test-retest reliability of myofascial trigger point detection in hip and thigh areas. Issue 4 (October 2017) - Rozenfeld, E.; Finestone, A.S.; Moran, U.; Damri, E.; Kalichman, L.
Abstract: Background: Myofascial trigger points (MTrP's) are a primary source of pain in patients with musculoskeletal disorders. Nevertheless, they are frequently underdiagnosed. Reliable MTrP palpation is the necessary for their diagnosis and treatment. The few studies that have looked for intra-tester reliability of MTrPs detection in upper body, provide preliminary evidence that MTrP palpation is reliable. Reliability tests for MTrP palpation on the lower limb have not yet been performed. Objective: To evaluate inter- and intra-tester reliability of MTrP recognition in hip and thigh muscles. Design: Reliability study. Subjects: 21 patients (15 males and 6 females, mean age 21.1 years) referred to the physical therapy clinic, 10 with knee or hip pain and 11 with pain in an upper limb, low back, shin or ankle. Methods: Two experienced physical therapists performed the examinations, blinded to the subjects' identity, medical condition and results of the previous MTrP evaluation. Each subject was evaluated four times, twice by each examiner in a random order. Dichotomous findings included a palpable taut band, tenderness, referred pain, and relevance of referred pain to patient's complaint. Based on these, diagnosis of latent MTrP's or active MTrP's was established. The evaluation was performed on both legs and included a total of 16 locations in the following muscles: rectus femoris (proximal), vastus medialis (middle and distal), vastus lateralis (middle and distal) and gluteus medius (anterior, posterior and distal). Results: Inter- and intra-tester reliability (Cohen's kappa (κ)) values for single sites ranged from −0.25 to 0.77. Median intra-tester reliability was 0.45 and 0.46 for latent and active MTrP's, and median inter-tester reliability was 0.51 and 0.64 for latent and active MTrPs, respectively. The examination of the distal vastus medialis was most reliable for latent and active MTrP's (intra-tester k = 0.27–0.77, inter-tester k = 0.77 and intra-tester k = 0.53–0.72, inter-tester k = 0.72, correspondingly). Conclusions: Inter- and intra-tester reliability of active and latent MTrP evaluation was moderate to substantial. Palpation evaluation can be used for clinical diagnosis of MTrP's in the hip and thigh muscles. Significance: This study provides evidence that MTrP palpation is a moderately reliable diagnostic tool in the hip and thigh muscles and can be used in clinical practice and research.